The Mystified Unknown—Sacralizing Influence in Soviet Science, Religion, and Ideology - Maria Roginska (Religions)
This article investigates a distinctive discursive space within Soviet society where scientific inquiry and mystical thought coexisted, despite the state’s official commitment to atheism. Referred to as the mystified unknown, this space provides a framework for understanding the persistence and intertwining of religious and mystical elements within Soviet scientific discourse. By focusing on the concept of “influence”, the study examines discussions in Soviet psychology to demonstrate how the regime’s political need to influence the masses, coupled with its suspicion of foreign ideas and a covert desire to wield influence, shaped the development of certain scientific disciplines, particularly the imaginaries they produced. This environment, characterized by doublethink and secrecy, nurtured the growth of scientific fantasies and mysterious imaginaries, allowing mystical concepts to endure under the veneer of science. Consequently, Soviet society became more inclined to re-enchant science rather than uphold it strictly as a symbol of secularism.